The Efficiency Of High School Principals In Baghdad Governorate In Managing Incentives From The Point Of View Of Teachers - Faisal Ahmed, May (Opción, 2019)
A field study aimed at identifying the degree of efficiency of secondary school principals in Baghdad governorate in the management of incentives, and adopted the descriptive analytical approach. The research community, which consists of (3981) teachers, was selected. The sample was randomly select- ed by (7,913%) of the research community, with 315 teachers in Resafa / 1 and Karkh A questionnaire consisting of (40) items was distributed among the study areas. The researchers confirmed their sincerity and persistence. The data were analyzed using the SPSS program, and the questionnaire was applied in the first semester of the 2016-2017 academic years. And reached results which were analyzed and discussed according to the areas of the study organized (general standards, mechanisms, physical and financial incentives, and moral and administrative incentives)